Effect of Alpha-Phellandrene on Glucose Uptake and Adipogenesis in Insulin Resistant 3T3-L1 Adipocytes: an in vitro and in silico Approach - Seethalakshmi, Souprayen; Sarumathi, Ravishankar; Sankaranarayanan, Chandrasekaran (Asian Journal of Biological and Life Sciences)
Aim: The present study was designated to investigate the effect of alpha-phellandrene, a monoterpene presents in essential oils of mint, turmeric, black pepper, and cinnamon on adipocyte function under insulin resistant condition. Materials and Methods: Mature 3T3-L1 adipocytes were exposed to high glucose (25 mM) and 0.6 nm/L of insulin for 24 hr to convert to IR-3T3-L1 adipocytes. The adipocytes were grouped into group1: normal control, group 2: diabetic control, group 3: diabetic group treated with alpha- phellandrene (65 μM) and group 4: diabetic group treated with rosiglitazone (0.1 μM). Glucose uptake assay, triglyceride accumulation and the activity of glycerol-3-phosphate dehydrogenase were measured. The binding affinity of alphaphellandrene with PPARγ and SREBP-1c were analysed by docking studies by using Auto Dock vina (V. 4.0) in Pyrx software. Results: Glucose uptake, triglyceride accumulation and activity of glycerol- 3-phopshate dehydrogenase were found to be decreased in diabetic control when control to normal control group. Alpha-phellandrene at dose of 65 μM increased glucose uptake, enhanced glycerol-3-phosphate activity and triglyceride accumulation in adipocytes which were found to be comparable with the standard drug rosiglitazone. A high binding affinity of alpha-phellandrene with key transcription factors, PPARγ and SREBP-1c which are associated with adipogenesis and steroidogenesis were observed in molecular docking studies. Conclusion: These results suggest that alpha-phellandrene positively regulates adipocyte function and ameliorate dyslipidaemia and hyperglycaemia in type II diabetes mellitus.
Keywords: 3T3-L1 adipocytes; Alpha-phellandrene; Glucose uptake; PPARγ; SREBP-1c